Political ideologies of social workers: An under explored dimension of practice - Mitchell Rosenwald; Cheryl A. Hyde (Advances in Social Work, 2006)
This article explores relationships between social workers' political ideologies and the effects on practice. Self-administered surveys from 294 licensed social workers in a mid-Atlantic state generated quantitative and qualitative data on whether and to what extent their ideologies influenced professional practice. Findings suggest that while social workers largely believe that their political ideology is separate from their practice, those who identified with more liberal political ideologies claim they used their ideologies more in practice than those who were more conservative. Additionally, strategies for monitoring political ideology in practice are shared. Implications for practice include the need for practitioners' increased awareness of their political ideologies and the profession's responsibility for establishing venues in which the ideology -- practice link can be explored and debated.